ANALISIS FAKTOR YANG MEMPENGARUHI FRAUD DI BANK SYARIAH YANG TERDAFTAR DI BANK INDONESIA TAHUN 2016 - Geri Herdianto; Harun Delamat; Ahmad Subeki (Department of Accounting, Faculty of Economics, Universitas Sriwijaya, 2016)
The purpose of this study is to determine the influence of Syariah Compliance (Sharia Compliance) and Good Corporate Governance against the existence of FRAUD dibank Syariah registered in Bank Indonesia.The population in this study are all Sharia Commercial Banks (BUS) registered at Bank Indonesia from 2011 to 2015. Samples are selected using purposive sampling method. Total sample used in this research. 8 Sharia Commercial Bank with 5 years study period. The method of analysis used in this study is multiple regression processed using SPSS version 22.The results of this study indicate the compliance of shariah variables With proxy Profit Sharing Ratio has a negative effect on fraud on Ratio of Islamic Sharia Income, Investment Ratios of Islam and Islam Corporate governance has no effect on fraud on sharia banks.